4x+13=6x-47

Simple and best practice solution for 4x+13=6x-47 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+13=6x-47 equation:


Simplifying
4x + 13 = 6x + -47

Reorder the terms:
13 + 4x = 6x + -47

Reorder the terms:
13 + 4x = -47 + 6x

Solving
13 + 4x = -47 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
13 + 4x + -6x = -47 + 6x + -6x

Combine like terms: 4x + -6x = -2x
13 + -2x = -47 + 6x + -6x

Combine like terms: 6x + -6x = 0
13 + -2x = -47 + 0
13 + -2x = -47

Add '-13' to each side of the equation.
13 + -13 + -2x = -47 + -13

Combine like terms: 13 + -13 = 0
0 + -2x = -47 + -13
-2x = -47 + -13

Combine like terms: -47 + -13 = -60
-2x = -60

Divide each side by '-2'.
x = 30

Simplifying
x = 30

See similar equations:

| 10y=500 | | X-3(5)=11 | | 6c+1=2c+59 | | 5(2.1y+3)=36 | | -2+9=-7+2v | | 4y=18-(14y+16) | | 8+2r-4r=1-3r | | -2(0)+3y=-19 | | 8[8-k]=-2[k-5] | | 8=2q+-11 | | 7x-6=3(x+2)+10x | | D=Bak | | f(x)=2lx-1l+3 | | 5(x+8)=3x+9 | | .05a-3=0.3(2a-3) | | 9/4=45z | | 8/9x=4/9 | | 6(x-6)=-60 | | 2x-73=143-6x | | 80x-1000000=400000 | | 3+7x-2x+4=22 | | 18=s | | 7x^2+49x=-84 | | 7x+49x=-49 | | 3+7x-2x+4=2 | | x/-4=-177 | | 35/6x15/2 | | 0.8-2t=1-2t | | 5(0.3)= | | 4c+3c-5c= | | -8-5x^2=-29 | | 3xn+4=-6 |

Equations solver categories